IMPROVING LEGAL MEASURES TO COMBAT TRADEMARK INFRINGEMENT IN THE REPUBLIC OF UZBEKISTAN (The Conference Hub, 2025)
In recent years, the pace of economic growth and foreign investment in the Republic of Uzbekistan has been rapidly increasing. From this perspective, the protection of intellectual property—particularly trademarks—has become a crucial factor in ensuring a fair competitive environment and safeguarding business interests.